Carbon-based Co catalyst, preparation thereof and application of carbon-based Co catalyst in reaction for preparing high-carbon alcohol and co-producing high-carbon olefin from synthesis gas
By adopting a carbon-based ligand coordination strategy in the catalyst for directly preparing high-carbon alcohols and olefins with high selectivity in syngas, the problems of complex preparation and low selectivity of existing catalysts are solved, and efficient and stable preparation of high-carbon alcohols and olefins are achieved.
Patent Information
- Application Number
- CN202411597795.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-25
AI Technical Summary
The existing catalysts for directly preparing high-carbon alcohols and olefins with high selectivity for syngas have problems such as complex composition and preparation methods, complicated pretreatment steps, and low selectivity for high-carbon alcohols and olefins.
The strategy of carbon-based ligand coordination is adopted to coordinate carbon ligands, phosphorus carbon ligands or nitrogen carbon ligands with metals Co and Mn, which improves the ability of CO adsorption, dissociation and insertion of alkyl chains, enhances the carbon-carbon coupling ability of the catalyst and inhibits the hydrogenation reaction.
The conversion rate of CO and the selectivity of high-carbon alcohols and olefins are improved, the stability and reaction performance of the catalyst are enhanced, and the goal of efficient preparation of high-carbon alcohols and olefins is achieved.
Smart Images

Figure BDA0005127407770000061
Abstract
Description
Technical Field
[0001] The present invention relates to a highly efficient synthesis gas conversion catalyst with a special coordination structure, which is applied to catalyze the direct and highly selective preparation of high-carbon alcohols and co-production of high-carbon olefins from synthesis gas, and belongs to the field of energy chemical industry. In particular, it relates to a preparation method and application of a CoMn-XC catalyst with a special carbon-based ligand coordination structure. Background Art
[0002] Higher carbon alcohols generally refer to alcohols containing six or more carbon atoms and are highly valuable in the chemical, pharmaceutical and energy industries. 5+ =) usually refers to linear α-olefins with 5 or more carbon atoms, with the general formula RCH=CH2, where R represents an alkyl group. Among them, 1-hexene, 1-octene, 1-decene, etc. are used as important organic raw materials for comonomers of various polyethylenes. The polymerization products of 1-decene and 1-octene (poly α-olefins) can be used to synthesize high-quality lubricants and plasticizers; and C6-C 10 Linear α-olefins can also be used to produce sealants, adhesives, drilling fluids, etc. The synthesis of higher alcohols and olefins usually involves the direct conversion of syngas, a gas mixture mainly composed of CO and H2 from natural gas or coal. However, this reaction process is complicated and includes not only the reactions for the synthesis of higher alcohols, but also side reactions such as methanation, methanol synthesis, Fischer-Tropsch synthesis, and water-gas shift reaction. As a result, a variety of products are formed, including olefins, alkanes, aldehydes, and alcohols. The carbon chain growth in this process usually follows the Anderson-Schulz-Flory (ASF) distribution, which makes it challenging to achieve high selectivity for higher alcohols and olefins and control the carbon number distribution of the products.
[0003] At present, various types of high-carbon alcohol synthesis catalysts have been studied, including modified methanol synthesis catalysts, modified Fischer-Tropsch synthesis catalysts, rhodium-based catalysts and molybdenum-based catalysts. Among them, the modified cobalt-based Fischer-Tropsch synthesis catalyst represented by Co-Cu bimetallic catalyst has improved the C 2+ The selectivity of high carbon alcohols can be improved, but the conversion rate and stability of the catalyst are still poor. Therefore, it is necessary to change the structure, composition and reaction conditions of the catalyst to improve the selectivity of high carbon alcohols. In order to achieve the above purpose, it has been studied.
[0004] Patent CN 117680184 A reports a preparation method using urea precipitation and hydrothermal crystallization to obtain a catalyst (Urea-CuMM1M2 / KIT-6) with high activity nano components, which is beneficial to improve the selectivity of high carbon alcohols. However, the preparation method of the catalyst in the patent document is cumbersome, the obtained catalyst CO conversion rate is low, a large amount of CO2 by-products will be produced during the reaction, and the overall selectivity of alcohols is low. Patent CN 111905791 B discloses an iron-based catalyst for preparing high carbon alcohols from synthesis gas, the iron-based catalyst is reduced and nitrided, and the active phase is iron nitride. However, the coordination environment of Fe of the catalyst has been changing during the reaction process, so the activity and selectivity are unstable. At the same time, since it is an iron-based catalyst, there is a problem of high selectivity of by-product CO2. Patent CN 105664964B reports a mixed oxide catalyst for preparing high-carbon alcohols from synthesis gas, which is mainly composed of two metals, Cu and Co. The catalyst has the advantages of high activity and high total alcohol selectivity, but the metal copper is easily agglomerated and deactivated during the reaction, resulting in a short catalyst life. In summary, the synthesis gas preparation of high-carbon alcohol catalysts reported in the current patents generally have complex composition and preparation methods, cumbersome pretreatment steps, and low selectivity for high-carbon alcohols and olefins, and still need to be further improved. Summary of the invention
[0005] The purpose of the present invention is to adopt a strategy of carbon-based ligand coordination, coordinate carbon ligands, phosphorus-carbon ligands or nitrogen-carbon ligands with metal Co and Mn, improve the CO conversion rate and the selectivity of high-carbon alcohols and olefins by improving the ability of CO adsorption, dissociation and insertion into alkyl chains, and enhance the carbon-carbon coupling ability of the catalyst and inhibit the hydrogenation reaction to reduce the generation of CH4 by carbonizing the metal cobalt into cobalt carbide during the reaction, and at the same time utilize the coordination characteristics of the carbon-based ligand to keep the active center single during the reaction, easy to control and stable, thereby improving the stability of the catalyst.
[0006] Preparation process of CoMn-XC catalyst with carbon-based ligand coordination structure:
[0007] (1) mixing a soluble salt of Co and a soluble salt of Mn at a metal molar ratio of 10:1 to 50:1 to prepare a mixture;
[0008] The soluble salt of Co is one or more of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt hydrochloride; the soluble salt of Mn is one or more of manganese nitrate, manganese acetate, manganese chloride and manganese sulfate;
[0009] (2) ultrasonically treating the mixture obtained in step (1) at room temperature for 5-10 hours, vigorously stirring at 1500-3000 rpm for 5-10 hours, and then adding 5-30g of different carbon-based ligands; the carbon ligand precursor is one or more of glucose, citric acid, and activated carbon, the phosphorus-carbon ligand precursor is one or more of phytic acid, phosphoric acid, and triphenylphosphine, and the nitrogen-carbon ligand precursor is one or more of melamine, pyridine, and aniline; after mixing evenly, adding 1-20g of alkyl lithium initiator for coordination reaction;
[0010] (3) adding 50-100 ml of deionized water to the mixture treated in step (2), ultrasonically treating it at 35-50° C. for 6-10 hours, and then placing it in a hydrothermal reactor and treating it at 120-200° C. for 3-8 hours;
[0011] (4) filtering the mixture after the treatment in step (3), and then washing with deionized water to obtain a filter cake;
[0012] (5) Dry the filter cake obtained in step (4) in air at 60-120°C for 10-20h, and then calcine at 600-1200°C for 5-15h in a helium atmosphere to obtain a CoMn-XC catalyst; the gas space velocity is 2000-4000h -1 .
[0013] The CoMn-XC catalyst with a special carbon-based ligand coordination structure can be used in the synthesis gas conversion reaction to prepare high-carbon alcohols and co-produce high-carbon olefins. It is characterized in that the catalyst is first loaded into the constant temperature zone of the reaction tube, and the entire reaction tube is filled with quartz sand. Before use, the catalyst is activated in hydrogen or hydrogen-inert gas mixture at 300-600°C for 1-50h, and the gas space velocity is 200-10000h -1 After activation, the reaction conditions are adjusted to the specified conditions, wherein the volume ratio of H2 to CO in the synthesis gas is 1 to 10, the reaction temperature is 180 to 350°C, the reaction pressure is 0.5 to 10 MPa, and the synthesis gas space velocity is 500 to 8000 h -1 .
[0014] The beneficial effects of the present invention are as follows: a new catalyst preparation method is proposed, a catalyst coordinated by a variety of carbon-based ligands is successfully prepared, and the catalyst is applied to the reaction of preparing high-carbon alcohols and olefins by converting synthesis gas, and the CO conversion rate and the selectivity of high-carbon alcohols and olefins are improved by improving the ability of CO to adsorb, dissociate and insert into alkyl chains, and the carbon-carbon coupling ability of the catalyst can be enhanced and the hydrogenation reaction can be inhibited to reduce the generation of CH4 by in-situ carbonization of metal cobalt to cobalt carbide during the reaction process, and the coordination characteristics of the carbon-based ligand are utilized to keep the active center single during the reaction process, which is easy to control and stable. The stability of the catalyst is thereby improved, and the catalyst is stable for >1200h.
[0015] The catalyst has the advantages of stable structure, high CO conversion rate and selectivity for high-carbon alcohols and olefins, and stable reaction performance. At the same time, the coordination strategy has a certain universality, which is conducive to large-scale production. DETAILED DESCRIPTION
[0016] In order to better understand the present invention, the technical solution of the present invention is described in detail below in conjunction with embodiments. The embodiments do not limit the protection scope of the present invention.
[0017] Example 1
[0018] (1) Take 2g of cobalt nitrate hexahydrate and 0.3g of manganese acetate and dissolve them in 20ml of deionized water.
[0019] Mix well.
[0020] (2) The resulting mixture was ultrasonically treated for 10 h, then vigorously stirred at 1800 rpm for 8 h, and 10 g of citric acid was added. After stirring, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0021] (3) adding 60 ml of deionized water to the obtained reaction product, ultrasonically treating it at 40° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 150° C. for 6 h;
[0022] (4) filtering and washing the product to obtain a filter cake;
[0023] (5) The obtained filter cake was dried in air at 80°C for 12 h and finally dried in a helium atmosphere at a space velocity of 3000 h -1 , and calcined at 1000℃ for 10h to obtain CoMn-C catalyst.
[0024] The catalyst was first activated at 400 °C for 5 h under hydrogen conditions with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 260℃, the reaction pressure was 3MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0025] Example 2
[0026] (1) Dissolve 1.5 g of cobalt acetate and 0.1 g of manganese acetate in 20 ml of deionized water and mix well.
[0027] (2) After ultrasonic treatment of the obtained mixture for 8 hours, the mixture was vigorously stirred at 1800 rpm for 6 hours, and 8 g of glucose was added. After the stirring was completed, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0028] (3) adding 100 ml of deionized water to the obtained reaction product, ultrasonically treating it at 40° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 150° C. for 8 h;
[0029] (4) filtering and washing the product to obtain a filter cake;
[0030] (5) The obtained filter cake was dried in air at 100°C for 12 h and finally dried in a helium atmosphere at a space velocity of 3500 h -1 , and calcined at 1200℃ for 10h to obtain CoMn-C catalyst.
[0031] The catalyst was first activated at 450 °C for 5 h under hydrogen conditions with a gas space velocity of 1000 h -1 Then, the volume ratio of H2 to CO was 2, the reaction temperature was 280℃, the reaction pressure was 5MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0032] Example 3
[0033] (1) Dissolve 1.8 g of cobalt nitrate and 0.5 g of manganese acetate in 20 ml of deionized water and mix well.
[0034] (2) After ultrasonic treatment of the obtained mixture for 7 hours, the mixture was vigorously stirred at 1800 rpm for 6 hours, and 8 g of phytic acid was added. After the stirring was completed, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0035] (3) adding 100 ml of deionized water to the obtained reaction product, ultrasonically treating it at 50° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 180° C. for 6 h;
[0036] (4) filtering and washing the product to obtain a filter cake;
[0037] (5) The obtained filter cake was dried in air at 120°C for 15 h and finally dried in a helium atmosphere at a space velocity of 3500 h -1 , and calcined at 1100℃ for 10h to obtain CoMn-PC catalyst.
[0038] The catalyst was first activated under hydrogen conditions at 500 °C for 5 h with a gas space velocity of 1000 h -1 Then, the volume ratio of H2 to CO was 2, the reaction temperature was 260°C, the reaction pressure was 5MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0039] Example 4
[0040] (1) Dissolve 2.0 g of cobalt nitrate and 0.2 g of manganese acetate in 20 ml of deionized water and mix well.
[0041] (2) The resulting mixture was ultrasonically treated for 8 h, then vigorously stirred at 1800 rpm for 6 h, and 8 g of triphenylphosphine was added. After stirring, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0042] (3) adding 80 ml of deionized water to the obtained reaction product, ultrasonically treating it at 50° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 200° C. for 6 h;
[0043] (4) filtering and washing the product to obtain a filter cake;
[0044] (5) The obtained filter cake was dried in air at 120°C for 15 h and finally dried in a helium atmosphere at a space velocity of 3500 h -1 , and calcined at 1200℃ for 10h to obtain CoMn-PC catalyst.
[0045] The catalyst was first activated at 400 °C for 5 h under hydrogen conditions with a gas space velocity of 2000 h -1 Then, the volume ratio of H2 to CO was 2, the reaction temperature was 260°C, the reaction pressure was 7MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0046] Example 5
[0047] (1) Dissolve 2.5 g of cobalt nitrate and 0.3 g of manganese nitrate in 20 ml of deionized water and mix well.
[0048] (2) After ultrasonic treatment of the obtained mixture for 6 hours, the mixture was vigorously stirred at 2000 rpm for 6 hours, and 8 g of melamine was added. After the stirring was completed, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0049] (3) adding 80 ml of deionized water to the obtained reaction product, ultrasonically treating it at 50° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 200° C. for 8 h;
[0050] (4) filtering and washing the product to obtain a filter cake;
[0051] (5) The obtained filter cake was dried in air at 100°C for 15 h and finally dried in a helium atmosphere at a space velocity of 4000 h -1 , and calcined at 1000℃ for 15h to obtain CoMn-NC catalyst.
[0052] The catalyst was first activated at 400 °C for 5 h under hydrogen conditions with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 4, the reaction temperature was 260℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0053] Example 6
[0054] (1) Dissolve 2.0 g of cobalt nitrate and 0.3 g of manganese nitrate in 20 ml of deionized water and mix well.
[0055] (2) The resulting mixture was ultrasonically treated for 8 h, then vigorously stirred at 2000 rpm for 6 h, and 9 g of pyridine was added. After stirring, the mixture was mixed evenly, and 5 g of alkyl lithium initiator was added to carry out coordination reaction;
[0056] (3) adding 80 ml of deionized water to the obtained reaction product, ultrasonically treating it at 50° C. for 8 h, and then placing it in a hydrothermal reactor and treating it at 180° C. for 8 h;
[0057] (4) filtering and washing the product to obtain a filter cake;
[0058] (5) The obtained filter cake was dried in air at 100°C for 15 h and finally dried in a helium atmosphere at a space velocity of 4000 h -1 , and calcined at 1000℃ for 15h to obtain CoMn-NC catalyst.
[0059] The catalyst was first activated at 460 °C for 5 h under hydrogen conditions with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 4, the reaction temperature was 270℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.
[0060] Comparative Example 1
[0061] (1) Dissolve 2.5 g of cobalt nitrate hexahydrate and 0.1 g of manganese acetate in deionized water;
[0062] (2) The resulting mixture was ultrasonically treated for 10 h, and then vigorously stirred at 1800 rpm for 8 h before adding 10 g of carbon ligand. After stirring, the mixture was mixed evenly.
[0063] (3) filtering and washing the product to obtain a filter cake;
[0064] (4) The obtained filter cake was dried in air at 100°C for 13 h and finally dried in a nitrogen atmosphere at a space velocity of 3000 h -1 , and calcined at 900℃ for 12h to obtain CoMn / AC catalyst.
[0065] The catalyst was first activated at 450 °C for 6 h under hydrogen conditions with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 280℃, the reaction pressure was 4MPa, and the synthesis gas space velocity was 3000h -1 The reaction was carried out under the conditions of
[0066] Comparative Example 2
[0067] (1) Dissolve 1.5 g of cobalt nitrate hexahydrate and 0.1 g of manganese acetate in deionized water;
[0068] (2) adding 8 g of carbon ligand for impregnation;
[0069] (3) The obtained solid was dried in air at 120°C for 10 h and finally dried in a nitrogen atmosphere at a space velocity of 3000 h -1 , and calcined at 600℃ for 10h to obtain CoMn / AC-IM catalyst.
[0070] The catalyst was first activated at 450 °C for 10 h under hydrogen conditions with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 270℃, the reaction pressure was 4MPa, and the synthesis gas space velocity was 2500h -1 The reaction was carried out under the conditions of
[0071] Table 1 Catalyst CO hydrogenation reaction performance evaluation and product analysis.
[0072]
[0073] As can be seen from Table 1, compared with the traditional catalyst preparation methods of Comparative Examples 1 and 2, the carbon-based ligand-coordinated catalyst prepared by a special method in the embodiment of the present invention can improve the ability of CO adsorption, dissociation and insertion into alkyl chains, thereby improving the CO conversion rate and the selectivity of high-carbon alcohols and olefins, effectively regulating the product distribution, and at the same time utilizing the coordination characteristics of the carbon-based ligand to keep the active center single during the reaction, easy to control and stable.
[0074] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and any modifications, equivalent replacements, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based Co catalyst, characterized in that: The preparation process includes: (1) mixing a soluble salt of Co and a soluble salt of Mn at a metal molar ratio of 10:1-50:1 (preferably 20:1-40:1, more preferably 20:1-30:1) to prepare a mixture; (2) treating 5-20 g (preferably 5-15 g, more preferably 10-15 g) of the mixture obtained in step (1) by ultrasonic treatment at room temperature for 5-10 h (preferably 5-8 h, more preferably 6-8 h), vigorously stirring at 1500-3000 (preferably 2000-3000, more preferably 2500-3000) rpm for 5-10 h (preferably 6-9 h, more preferably 8-9 h), adding 5-30 g (preferably 10-30 g, more preferably 15-20 g) of precursors of different carbon-based ligands, mixing well, and adding 1-20 g (preferably 2-15 g, more preferably 4-10 g) of alkyl lithium initiator for coordination reaction; (3) adding 50-100 ml (preferably 70-100 ml, more preferably 70-90 ml) of water to the mixture after treatment in step (2), and ultrasonically treating the mixture at 35-50° C. (preferably 40-50° C., more preferably 40-45° C.) for 6-10 hours (preferably 7-10 hours, more preferably 8-10 hours), and then placing the mixture in a hydrothermal reactor and treating it at 120-200° C. (preferably 140-200° C., more preferably 140-180° C.) for 3-8 hours (preferably 4-8 hours, more preferably 5-8 hours); (4) filtering the mixture after the treatment in step (3), and then washing with water to obtain a filter cake; (5) Drying the filter cake obtained in step (4), and then calcining it at 600-1200° C. (preferably 800-1100° C., more preferably 900-1000° C.) for 5-15 h (preferably 8-13 h, more preferably 8-10 h) under an inert atmosphere to obtain a CoMn-XC catalyst.
2. The preparation method according to claim 1, characterized in that: The carbon-based ligand precursor includes one or more of a carbon ligand precursor, a phosphorus-carbon ligand precursor, and a nitrogen-carbon ligand precursor; The carbon ligand precursor is one or more of glucose, citric acid, and activated carbon; The phosphorus-carbon ligand precursor is one or more of phytic acid, phosphoric acid, and triphenylphosphine; The nitrogen-carbon ligand precursor is one or more of melamine, pyridine and aniline.
3. According to the preparation method of claim 1, the soluble salt of Co is one or more of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt hydrochloride; the soluble salt of Mn is one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate.
4. The preparation method according to claim 1, characterized in that: The obtained filter cake is dried in air at 60-120℃ for 10-20h, with a gas space velocity of 2000-4000h -1 (Preferably 2000-3000h -1 , more preferably 2000-2500h -1 ); The inert atmosphere is one or more of helium, nitrogen and argon.
5. A catalyst prepared by the preparation method according to any one of claims 1 to 4.
6. The catalyst according to claim 5, characterized in that: The catalyst consists of an active center, an auxiliary component and a carbon-based ligand, wherein the active component is a single atom, nanoparticle or carbide of Co, the auxiliary component is a simple substance or oxide of Mn, the carbon-based ligand is a carbon ligand, a phosphorus-carbon ligand or a nitrogen-carbon ligand, the carbon ligand precursor is one or more of glucose, citric acid and activated carbon, and the high reaction activity site is Co-Co2C coordinated by the carbon-based ligand and separate Co and Mn species.
7. Use of the catalyst according to claim 5 or 6 in catalyzing the preparation of higher carbon alcohols and co-production of higher carbon olefins from synthesis gas.
8. The use according to claim 7, characterized in that The catalyst is reduced and activated before use, the reducing gas is hydrogen or a hydrogen-inert gas mixture, usually the reducing gas is hydrogen or a hydrogen-nitrogen mixture (the volume ratio of hydrogen to nitrogen is 1% to 99% (preferably 10% to 70%, more preferably 20% to 60%)), the reduction activation temperature is 300 to 600° C. (preferably 400 to 600° C., more preferably 500 to 600° C.), the reduction activation time is 1 to 50 h (preferably 10 to 40 h, more preferably 20 to 40 h), the gas space velocity is 200-10000 h -1 (Preferably 1000-8000h -1 , more preferably 2000-6000h -1 ).
9. The use according to claim 7 or 8, characterized in that The volume ratio of H2 to CO in the synthesis gas is 1 to 10 (preferably 2 to 8, more preferably 4 to 6), the reaction temperature is 180 to 350°C (preferably 200 to 320°C, more preferably 220 to 300°C), the reaction pressure is 0.5 to 10 MPa (preferably 2 to 8 MPa, more preferably 4 to 8 MPa), and the synthesis gas space velocity is 500 to 8000 h -1 (Preferably 1000~6000h -1 , more preferably 2000 to 5000 hours -1 ).
10. The use according to claim 7 or 8, characterized in that: Higher carbon alcohols refer to alcohols with six or more carbon atoms, and higher carbon olefins refer to α-olefins with five or more carbon atoms.
Citation Information
Patent Citations
A mixed oxide catalyst for the preparation of higher alcohols from syngas
CN105664964B
A catalyst for the preparation of higher alcohols from syngas and its preparation method
CN111905791B
Catalyst for directly preparing high-carbon alcohol from synthesis gas as well as preparation method and application of catalyst
CN117680184A